Philosophical skepticism as the subject of art Maria Bussmann's drawings - Carrier, David 1944- (Bloomsbury Academic, 2023)
"The artwork of Maria Bussmann, a trained academic German philosopher and a significant visual artist, provides an ideal test case for a philosophical study of visual art. Bussmann has internalized the relationship between art and philosophy. In this exploration of the history of German aesthetics through Bussmann's work, David Carrier places the philosophical tradition in the context of contemporary visual culture. Each chapter focuses on the arguments of a major philosopher whose concerns Bussmann has dealt with as an artist: Kant, Hegel, Merleau-Ponty, Wittgenstein and Arendt. Offering comparative accounts of artists and philosophers whose work is of especial relevance, Carrier shows how Bussmann responds visually to writings of philosophers in art that has an elusive but essential relationship to theorizing. Tackling the question of whether philosophical subjects can be presented visually, Carrier offers a fresh perspective on the German idealist position through the visual art of 21st-century artist steeped in the tradition and continually challenging it through her work"--
Keywords: Bußmann, Maria -- 1966-; Zeichnung; Philosophie; Skeptizismus; Bussmann, Maria / 1966- / Criticism and interpretation; Bussmann, Maria / 1966-; Criticism, interpretation, etc